Safety and Efficacy of Multilamellar Liposomal Nystatin against Disseminated Candidiasis in Persistently Neutropenic Rabbits - Groll, Andreas H. (American Society for Microbiology, 1999)
The activity of liposomal nystatin (L-Nys) against subacute disseminated candidiasis was investigated in persistently neutropenic rabbits. Antifungal therapy was administered for 10 days starting 24 h after intravenous inoculation of 10(3) blastoconidia of Candida albicans. Responses to treatment were assessed by the quantitative clearance of the organism from blood and tissues. Treatments consisted of L-Nys at dosages of 2 and 4 mg/kg of body weight/day (L-Nys2 and L-Nys4, respectively) amphotericin B deoxycholate at 1 mg/kg/day (D-AmB), and fluconazole at 10 mg/kg/day (Flu). All treatments were given intravenously once daily. Compared to the results for untreated but infected control animals, treatment with L-Nys2, L-Nys4, D-AmB, and Flu resulted in a significant clearance of the residual burden of C. albicans from the kidney, liver, spleen, lung, and brain (P < 0.0001 by analysis of variance). When the proportion of animals infected at at least one of the five tissue sites studied was evaluated, a dose-dependent response to treatment with L-Nys was found (P < 0.05). Compared to D-AmB-treated rabbits, mean serum creatinine and blood urea nitrogen levels at the end of therapy were significantly lower in animals treated with L-Nys2 (P < 0.001) and L-Nys4 (P < 0.001 and P < 0.01, respectively). L-Nys was less nephrotoxic than conventional amphotericin B and had dose-dependent activity comparable to that of amphotericin B for the early treatment of subacute disseminated candidiasis in persistently neutropenic rabbits.